2018
DOI: 10.1186/s12929-018-0490-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of highly active antiretroviral therapy on the serum levels of pro-inflammatory and anti-inflammatory cytokines in HIV infected subjects

Abstract: BackgroundCytokines play an important role in controlling the homeostasis of the immune system and infection with Human Immunodeficiency virus (HIV) leads to deregulated production of both pro- and anti-inflammatory cytokines. This study was designed to determine the effects of HIV and Highly Active Antiretroviral Therapy (HAART) on the levels of pro-and anti-inflammatory cytokines in HIV infected subjects.MethodA total of 50 HIV infected and 50 HIV seronegative control participants were recruited for the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 29 publications
10
63
3
2
Order By: Relevance
“…One of these studies showed that upon Schistosoma mansoni infection, the IL‐4 cytokine upregulates miR‐182 expression Th2‐Treg cells, thereby suppressing IL‐2 secretion of the Th1 response . Another found the IL‐4 cytokine in significantly higher levels in HIV mono‐infected subjects . In the present study, there was no correlation between miR‐182 and cytokines.…”
Section: Discussioncontrasting
confidence: 45%
“…One of these studies showed that upon Schistosoma mansoni infection, the IL‐4 cytokine upregulates miR‐182 expression Th2‐Treg cells, thereby suppressing IL‐2 secretion of the Th1 response . Another found the IL‐4 cytokine in significantly higher levels in HIV mono‐infected subjects . In the present study, there was no correlation between miR‐182 and cytokines.…”
Section: Discussioncontrasting
confidence: 45%
“…The abnormally hyper activation of immune system has been widely reported in viral infection including HIV-1 and significantly correlated with the severity of the disease [ 40 , 41 ]. Previously, it has been shown that HIV-1 Tat induces the expression of pro-inflammatory molecules like IL-6 and IL-8 in both human monocytes and dendritic cells of HIV-1 patients [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fewer CD4-positive cells may prevent IL-2 and IFN-γ secretion, 26 even after a lengthy period of antiretroviral therapy. 27 Hence, it is possible that lower levels of pro-inflammatory cytokines, particularly IFN-γ, can affect the tumor microenvironment and lead to a decrease in PD-L1 expression in tumor cells or immune cells of HIV patients. In addition, some studies have demonstrated that several signalling genes, such as NF-κB, MAPK, and JAK/STAT, are also down-regulated after ART.…”
Section: Discussionmentioning
confidence: 99%